Thailand : Financial Sector Assessment Program; Detailed Assessment of Observance of Thailand Securities Depository (TSD) of the CPSS/IOSCO Recommendations for Securities Settlement Systems. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses the assessment of observance of Thailand Securities Depository (TSD) of the Committee of Payments and Settlement Systems (CPSS)/International Organization of Securities Commissions (IOSCO) recommendations for securities settlement systems for Thailand. On the basis of the assessment, it is recommended that securities settlement systems should have a well-founded, clear, and transparent legal basis in the relevant jurisdiction. Confirmation of trades between market participants should occur as soon as possible after trade execution, but no later than the trade date (T+0).